The Influence of Tourism Visits on Community Welfare Around Tourist Attractions An Islamic Perspective (Community Service in Karangpanimbal Village, Purwaharja District) - Sumarni, Sumarni; Ramdhani, Eggy Armand; Akasah, Usep Nur; Muslih, Agus Fuad; Sulastri, Depi; Amanda, Dhea; Nuramalia, Mila (Khidmat, 2024)
The tourism sector is one of the people's economic potentials that needs to be developed in order to improve community welfare and regional development. This is a positive influence on tourism businesses in improving relations with the community to improve the welfare of the people around the tourist attraction. According to the Islamic view, social welfare is the realization of human goals to achieve happiness in the world and the hereafter (Falah) as well as a good and honorable life (al-hayah al-tayyibah). The problem formulation in this research is whether tourist visits affect the welfare of the community around the tourist attraction and how the welfare of the community around the tourist attraction is viewed from an Islamic economic perspective, while the aim of this research is to find out whether tourist visits have an effect on the welfare of the community around the tourist attraction and to find out how the welfare of the community around the tourist attraction area is viewed from an Islamic economic perspective. The method used in this research is a case study, a descriptive research method. The data used uses primary and secondary data.